PENDIDIKAN MANAJEMEN DIRI, INFORMASI, DAN BUDAYA KUNCI PEMBINAAN PRODUKTIVITAS KAUM WANITA - Mundilarno, Mundilarno (Jurnal Penelitian Humaniora, 2015)
Abstract In globalization era the quality of human resource is the most important factor. A qualified person will show that he or she is productive and do anything effectively and efficiently. Information in the globalization era has a very strategic role. So that a productive people will manage him/ herself, information, time, knowledge and ability good. In connection with every one do anything cannot be isolated with the culture, the productivity of someone or community thus will also depend on their ability to manage the culture values and themselves. A productive person thus should manage his time, information, knowledge, skill, resources, habits and culture to fulfill needs efficiently and effectively. A qualified people need help and supports and education. They cannot grow up automatically. In other words every one or community must be supervised, touch, and educated in order to be productive. The concept of andragogy may use to educate nonproductive women. The case of research results on the women in the destitute areas in the Special Province of Yogyakarta shows that to productivity, the quality of management of self has effective contribution of 7.5% and the quality of the management of informationhas effective contribution of 46.2% and the quality of management of culture has effective contribution 4%. The research results and the concepts decribed above show that how to improve the productivity of human resources include of nonproductive women must done by cultural approach, education and by improving the ability in managing self and information. Keywords: poverty culture, productivity, self-management ability, educational approach, and supervision